2016
DOI: 10.1186/s12985-016-0621-4
|View full text |Cite
|
Sign up to set email alerts
|

Serosurveillance of viral pathogens circulating in West Africa

Abstract: BackgroundSub-Saharan Africa is home to a variety of pathogens, but disease surveillance and the healthcare infrastructure necessary for proper management and control are severely limited. Lassa virus, the cause of Lassa fever, a severe hemorrhagic fever in humans is endemic in West Africa. In Sierra Leone at the Kenema Government Hospital Lassa Diagnostic Laboratory, up to 70 % of acute patient samples suspected of Lassa fever test negative for Lassa virus infection. This large amount of acute undiagnosed feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 33 publications
2
45
0
1
Order By: Relevance
“…In these rodents, the virus exhibits persistent, asymptomatic infection. Due to their ubiquitous geographic distribution across the West African region, the population-at-risk for Lassa fever is estimated at nearly 60 million people [3,4,7]. LASV fever cases are typically the result of rodent-tohuman transmission events, facilitated by contact with infectious rodent urine or faeces in the household environment [2].…”
Section: Viral Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…In these rodents, the virus exhibits persistent, asymptomatic infection. Due to their ubiquitous geographic distribution across the West African region, the population-at-risk for Lassa fever is estimated at nearly 60 million people [3,4,7]. LASV fever cases are typically the result of rodent-tohuman transmission events, facilitated by contact with infectious rodent urine or faeces in the household environment [2].…”
Section: Viral Ecologymentioning
confidence: 99%
“…Lassa fever is endemic to several West African countries. Sierra-Leone, Liberia, Guinea, and Nigeria are most heavily affected; however, LASV infections have also been detected throughout the Côte d'Ivoire, Togo, Benin, Ghana, Central African Republic, Democratic Republic of Congo, Senegal, and southern Mali [4][5][6][7]. As a nonspecific febrile illness with a high proportion of asymptomatic cases, LASV infection is often unreported or misdiagnosed, precluding accurate determination of its true burden.…”
Section: Introductionmentioning
confidence: 99%
“…This assay has lower limits of detection for Lassa virus nucleoprotein and IgM than traditional ELISAs (53). The same group also developed and tested a multiplex MAGPIX IgG assay for a wide spectrum of hemorrhagic fever viruses, including alphaviruses, arenaviruses, flaviviruses, and filoviruses (14). Further development of multiplex MAGPIX assays, including testing for Lassa virus antigen and common endemic diseases such as malaria, would assist with the diagnosis and clinical management of suspected Lassa fever cases, especially in scenarios of coinfection with Lassa virus and bacterial or parasitic organisms where multiple therapeutic modalities may be indicated.…”
Section: Antigen and Antibody Detection Assaysmentioning
confidence: 99%
“…While the detection of a new positive IgG titer combined with an IgM response in the correct clinical setting may support a diagnosis of Lassa fever, the detection of a positive IgG response alone is insufficient to make a diagnosis. Lassa IgG titers may persist for decades (64), and seroprevalence studies in regions of endemicity have shown 4 to 55% of healthy individuals living in areas where the virus is endemic have detectable Lassa virus IgG titers (14,52,55,65,66).…”
Section: Antigen and Antibody Detection Assaysmentioning
confidence: 99%
“…1 The impact of LASV on the public health resources in these countries is significant with an estimated 10-30% of adult hospital admissions and 14% of all febrile disease attributed to LASV infection. [2][3][4] Recent ecological studies conducted in response to the identification of sporadic cases of Lassa fever in other west African countries including Benin, Togo, Ghana, Cote d'Ivoire, and Mali suggest a larger region where LASV is circulating. [5][6][7][8][9][10][11] As a result, it is likely that the overall burden of LASV infection across west Africa is underestimated.…”
mentioning
confidence: 99%